If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(7 + -3v) = -2 (7 * -2 + -3v * -2) = -2 (-14 + 6v) = -2 Solving -14 + 6v = -2 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 6v = -2 + 14 Combine like terms: -14 + 14 = 0 0 + 6v = -2 + 14 6v = -2 + 14 Combine like terms: -2 + 14 = 12 6v = 12 Divide each side by '6'. v = 2 Simplifying v = 2
| 0.10(x-5)=2.40 | | -5(c-2)=30+5c | | 5t-8+4t=19 | | -5x+3x=-12 | | 12=12b-4 | | 44=-7x-3(-x-4) | | -15+23=-2(x-8) | | -24=-8k-4k | | 6r^2+36=-33r | | a-4-2=-6 | | 2400+250x=6000 | | 4x-(x+2)= | | 232=40t | | 4G=20 | | 5=-7x+6x | | 5x-3(x-3)=-7+4x+10 | | 232=40*t | | y^4=16y | | 49x+11=6(7x+2)+7x-1 | | -9x-5y-6y= | | 4(n-3)=-15 | | (8-x)2=24 | | n-1-5=-10 | | 1+n+4n=16 | | y=5x^2+24x+27 | | 7x+4=7x+17 | | -4x+3(-x+14)=91 | | -20=-8p+6-2 | | -45=-10x-3 | | 5x+28=49-7x | | 3+4n=-5 | | 7+5m=3m-5 |